Uji Efektivitas Penggunaan LKPD Ketahanan Pangan (Peternakan) Berbasis Bacaan Kontekstual untuk Meningkatkan Keterampilan Membaca Siswa Kelas III di SDN Kandangan II - Az-Zahra, Aulia Rahmatunissa'; Istiq’faroh, Nurul; Nihla, Syifda Aulia (Jurnal Ilmu Sosial dan Budaya Indonesia, 2026)
Reading comprehension is a fundamental skill that must be mastered by elementary school students; however, many students still experience difficulties in understanding written texts. This issue is often caused by the lack of contextual and engaging instructional materials. Therefore, this study aims to examine the effectiveness of using contextual reading-based student worksheets (LKPD) on food security (livestock) in improving the reading comprehension skills of third-grade students at SDN Kandangan II. This study employed a quantitative approach with a pre-experimental design using a one-group pretest-posttest design. The subjects of this study were 25 students. Data were collected through tests (pre-test and post-test) and documentation. The data were analyzed using a normality test, N-Gain test, and Wilcoxon Signed Rank Test with the assistance of IBM SPSS Statistics 29. The results showed that the average pre-test score was 73.96, while the post-test score increased to 81.36, indicating an improvement of 7.4 points or 10.01%. The normality test results indicated that the data were not normally distributed; therefore, the Wilcoxon test was used as a non-parametric alternative. The Wilcoxon test results showed a significance value of less than 0.05, indicating a significant difference between pre-test and post-test scores. In conclusion, the use of contextual reading-based LKPD on food security (livestock) is effective in improving elementary students’ reading comprehension skills.Keywords: contextual reading, reading comprehension, food security, student worksheet, elementary school